2021
DOI: 10.3390/su13158458
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Chemical Properties of Banana Pseudostem, Mushroom Media Waste, and Chicken Manure through the Co-Composting Process

Abstract: Co-composting is an effective approach to biowaste management. The co-composting potential of banana pseudostem (BPS) and mushroom media waste (MMW) with chicken manure (CM) has not been explored, let alone their suitable ratios of co-composting being determined. Meanwhile, the imbalance ratios of the feedstocks used in the process severely restrict the physicochemical properties and quality of the finished product. For this reason, six different ratios of BPS, MMW, and CM, viz. 1:1:1, 1:2:1, 1:3:1, 2:1:1, 2:2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…The protein, amino acids, phenolic contents, and sugar contents are the major indicator of the quality of sweet corn which is governed by the availability of nutrients either from soil-applied fertilizers and/or foliar fertilization. In our study, the foliar-applied banana pseudostem sap was rich in K, Ca, and Mg as well as contain some extent of micronutrients ( Table 2 ) that was in agreement with Islam et al [ 14 ]. Moreover, inherent nutrients with enriched N, P, K, and B in the banana pseudostem sap created an enriched liquid fertilizer ( Table 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…The protein, amino acids, phenolic contents, and sugar contents are the major indicator of the quality of sweet corn which is governed by the availability of nutrients either from soil-applied fertilizers and/or foliar fertilization. In our study, the foliar-applied banana pseudostem sap was rich in K, Ca, and Mg as well as contain some extent of micronutrients ( Table 2 ) that was in agreement with Islam et al [ 14 ]. Moreover, inherent nutrients with enriched N, P, K, and B in the banana pseudostem sap created an enriched liquid fertilizer ( Table 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…For this reason, Antalya and Mersin provinces were chosen as the study area in determining the biomass (banana waste) potential that can be obtained from banana cultivation (Figure 1). The chemical and physical characteristics of the analyzed waste are similar to the results developed by Martin [30], Jewiarz et al [34], and Islam et al [35], who showed a greater C:N ratio (73.2). According to Khan et al [36], methane yields ranged between 223 and 336 L•kg −1 volatile solids (VS) for banana peel, and between 188 and 334 L•kg −1 VS for banana stalk, respectively, while banana flesh may have reached almost 400 L•kg −1 VS.…”
Section: Data For Calculations and Formulassupporting
confidence: 86%
“…Rice bran addition in Tr_4 and Tr_5 (50%, w/w) generally enhanced the germination index and the growth of radish and pepper. Islam et al [58] reported that the GI of radish seeds for compost with the chicken manure was 130%. The GI of radish seeds for Tr_5 in this study was much higher (297%).…”
Section: Discussionmentioning
confidence: 99%